2008
DOI: 10.1128/jb.01523-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Type 3 Fimbriae in UropathogenicEscherichia coliReveals a Role in Biofilm Formation

Abstract: Catheter-associated urinary tract infection (CAUTI) is the most common nosocomial infection in the UnitedStates. Uropathogenic Escherichia coli (UPEC), the most common cause of CAUTI, can form biofilms on indwelling catheters. Here, we identify and characterize novel factors that affect biofilm formation by UPEC strains that cause CAUTI. Sixty-five CAUTI UPEC isolates were characterized for phenotypic markers of urovirulence, including agglutination and biofilm formation. One isolate, E. coli MS2027, was uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 63 publications
8
93
0
2
Order By: Relevance
“…Furthermore, type 3 fimbriae have been established to play a significant role in K. pneumoniae biofilm formation (9,20,27). Historically, type 3 fimbriae have not been associated with E. coli; however, most recently two independent studies have reported type 3 fimbria expression in E. coli strains (3,36). Intriguingly, in both studies type 3 fimbriae were encoded by conjugative plasmids and found to profoundly enhance the ability of E. coli to form biofilm.…”
mentioning
confidence: 92%
“…Furthermore, type 3 fimbriae have been established to play a significant role in K. pneumoniae biofilm formation (9,20,27). Historically, type 3 fimbriae have not been associated with E. coli; however, most recently two independent studies have reported type 3 fimbria expression in E. coli strains (3,36). Intriguingly, in both studies type 3 fimbriae were encoded by conjugative plasmids and found to profoundly enhance the ability of E. coli to form biofilm.…”
mentioning
confidence: 92%
“…Other groups have also shown that capsule expression can affect the biofilm formation of pathogens such as Vibrio vulnificus (45) and Porphyromonas gingivalis (46). For example, capsule synthesis genes (wza and wzc for K. pneumoniae and kpsM for E. coli) were recently shown to negatively affect biofilm formation (47,48). In contrast, our acapsular mutant, strain 33.2, produced a biofilm similar to that formed by the parental A. pleuropneumoniae strain, even though the former exhibited enhanced adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Surface polysaccharides, including LPS, CPS, and PGA, have been linked to biofilm formation in several bacterial species (17,25,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51); thus, investigation of their unassessed role in the biofilm formation of A. pleuropneumoniae serotype 1 was the focus of our present study. LPS and CPS have been implicated in both the adhesion and virulence of A. pleuropneumoniae, but their role in biofilm formation is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of the biofilm is essential for the development of CAUTI [7]. Factors within the bladder accumulate on the surface of the catheter and facilitate biofilm formation.…”
Section: Introductionmentioning
confidence: 99%